Effects of Soy Protein and Rice Protein on Stability and Pasting Properties of Brown Rice Beverage - Nitisuk, Panorjit; Uriyapongson, Juntanee; Alli, Inteaz (Food and Applied Bioscience Journal, 2018)
The objective of this research was to investigate the effects of protein addition on the viscosity, pasting properties, suspension stability and storage stability of brown rice beverage. In this study, six protein ingredients, including soy flour, soy protein isolate (SPI) and rice protein extracts (albumin, globulin, glutelin and prolamin) were used at two concentrations (0.5 and 1.0%, w/w). The non-pasteurized beverages subject to the addition of 1.0% SPI and 0.5% prolamin and measured by RVA showed the highest peak of viscosity, final viscosity and setback. Meanwhile, the pasteurized samples at temperature 4 °C showed higher viscosity than those at 25 °C. The addition of SPI 1.0% at temperature 4 °C demonstrated the highest viscosity, followed by 0.5% addition. The samples added with 1.0% of soy flour and SPI, and 0.5% of prolamin gave the highest suspension and storage stability, compared to those of the control and other protein extracts. This study has demonstrated that prolamin from rice extract should be considered as suitable protein addition for brown rice beverage to improving its small particles, suspension stability and storage stability.